HIGH-RESOLUTION TRANSMISSION ELECTRON MICROSCOPY OF MIXED-LAYER CLAYS DISPERSED IN PVP-10: A NEW TECHNIQUE TO DISTINGUISH DETRITAL AND AUTHIGENIC ILLITIC MATERIAL - Uhlik P.; Sucha V.; Elsass F.; Caplovicova M. (My University, 2000)
The results of a new technique for the measurement of the thickness distribution of fundamental particles are reported. The technique is based on high-resolution transmission electron microscopy (HRTEM) of Na-saturated mixed-layer illite-smectite dispersed in polyvinylpyrrolidone (PVP-10). Intercalation of PVP-10 increases the spacing of expandable interlayers and changes the arrangement of particles so that the number of layers per fundamental particle can be counted easily on HRTEM images. The data obtained by HRTEM on PVP-10-intercalated illite-smectite of hydrothermal origin are compared with data from the Pt-shadowing technique. A good agreement between the two methods for the measured thickness distributions, mean thickness and expandability confirms the reliability of the new technique. The same technique is applied to a set of four sedimentary samples with different expandabilities (83-18%). The thickness of illite particles from shales and claystones has a lognormal distribution. Detrital and discrete illite particles can be distinguished from the thickness distribution of authigenic illite.